The Development of Reflective Practices for Islamic Religious Education Teachers - Yedi Purwanto; Aep Saepudin; Sofaussamawati Sofaussamawati (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2023)
Continuous professional development for teachers is crucial in order to enhance their competence and professionalism. It is equally important for student teacher candidates to engage in field practice activities that promote self-reflection. The main objective of this research is to investigate how self-reflection among prospective Islamic Religious Education teachers contributes to the development of their professionalism. The study involved six participants from two universities, namely Unisba (Universitas Islam Bandung) and UPI (Universitas Pendidikan Indonesia). Qualitative methods were employed, utilizing case studies based on Stake's approach (1978). The data collection process involved interviews, observations, and documentation techniques. The analysis was conducted through several stages, including data reduction, presentation, and drawing conclusions. The results reveal that reflective practice enhances pedagogical competence by implementing high-quality, innovative, and creative teaching methods, particularly within the classroom setting. These findings have practical implications for the field practice of Islamic Religious Education teachers in schools. They serve as a valuable resource for teachers to develop new strategies in addressing challenges within the teaching and learning process, ultimately contributing to their professional growth and establishing cultural references.